Australian music teachers’ reflections and concerns during the pandemic: Resetting the use of technologies in 21st century classroom practice - Dawn Joseph; Bradley Merrick (New Zealand Journal of Teachers' Work)
Classroom practice around the globe has changed considerably due to the global pandemic. Although ICT (information and communication technology) is at the heart of 21st century teaching and learning, many teachers and students had to make significant adjustments shifting from face-to-face to remote (online) delivery in response to lockdowns and government restrictions since March 2020. This paper focuses on one focal question: ‘What were some of the concerns using ICT during Covid-19 pandemic?’ which was part of a wider Australian study ‘Re-imaging the future: music teaching and learning, and ICT in blended environments in Australia’. The authors seek to understand how music teachers look to employ technology in ways that connect teaching frameworks to 21st century classroom practice. As part of the ongoing study, they present preliminary survey data gathered between March–June 2021 from a range of music teachers around the country. Using thematic analysis, they discuss advantages, disadvantages, opportunities, and challenges in relation to responses that thematically relate three key elements: pedagogy, social interaction, and technology. They identify concerns and call on music educators to reset what, how, and why they teach when using technology to develop 21st century competencies, as the future of schooling continues to change its landscape due to the pandemic.